Great or nothing - McCullough, Joy; Sharpe, Tess; Spotswood, Jessica; Richmond, Caroline Tung (Delacorte Press, 2022)
"A reimagining of Little Women set in the spring of 1942, when the United States is suddenly embroiled in the Second World War, this story, told from each March sister's point of view, is one of grief, love, and self-discovery"--